Numerical solution of the boundary value problems for the parabolic equation with involution - A. Ashyralyev; C. Ashyralyyev; A.M.S. Ahmed (Қарағанды университетінің хабаршысы. Математика сериясы, 2023)
In this work, we study two boundary value problems for involutary parabolic equation with the first and second kind conditions. We propose absolute stable difference schemes for numerical solutions of these boundary value problems. Actually the stability estimates for solutions of difference schemes are proved. Later error analysis for the numerical solution of both difference schemes are illustrated by test examples.